Pengaturan Hukum Penyalahgunaan Data Pribadi Penyandang Disabilitas Fisik di Era Digital - Suzana, Merillyn Victoria; Michael, Tomy (Media Hukum Indonesia (MHI), 2024)
This article examines the legal framework regarding the misuse of personal data of persons with physical disabilities in Indonesia, as well as the state's efforts to provide protection through existing regulations, such as Law No. 27 of 2022 on Personal Data Protection (UU No. 27/2022) and Law No. 8 of 2016 on Persons with Disabilities (UU No. 8/2016). The misuse of personal data can harm persons with disabilities in various ways, such as affecting their access to social assistance, healthcare, and other services guaranteed by law. Additionally, this article highlights the protection of human rights for persons with physical disabilities based on the principle of non-discrimination as outlined in the Universal Declaration of Human Rights and the International Covenant on Civil and Political Rights (ICCPR). Although Law No. 27/2022 has been enacted to provide a legal basis for personal data protection. Through a normative legal approach, this article emphasizes the importance of strengthening legal protection for the personal data of persons with physical disabilities in Indonesia to ensure their rights to privacy and equal access to services provided by the state. Fulfilling the right to personal data protection is part of the effort to create a safe and inclusive environment for persons with physical disabilities in Indonesia.